(untitled) (Biological Sciences - PJSIR, 1996)
Four isonitrogenous (38% protein) diets were prepared using fish meal, silkworm pupae (Bombyx mori), mus- tard oil cake (Brassica )uncea) and maskali bran (Phaseolus mungo) as dietary protein sources. Silkworm pupae (SWP) was included in the diets at 40,30 and.20% of dietary level of protein in the diet 2, 3 and 4 respectively. The dietary protein frommustard oil cake and maskali bran were kept constant.These diets weretested in cistern tank for 77 days to evaluate the low-cost silkworm pupae meal in the diet of mirror carp (Cyprinus carpio L.) and growth response of fish fed these diets were compared to fish fed a fish mealbased control diet (diet 1).Diet 2 and 3 showed significantly (P < 0.05) higher growth performance followed by diet 4. The control diet without silkworm showed poorest growth performance. Body lipid andprotein content offish werefound to increase in fish fedhigher levels of SWP based diets. The results of the study indicate the possibility of replacing the costly fish meal with silkworm pupae in formulating low-cost diet for mirror carp.